WHAT IS LIFE AND WHEN DOES BEGIN? REFLECTIONS ON EMBRYO ONTOLOGY - Carlos de Aquino Almeida, João (LINKSCIENCEPLACE, 2026)
Often researchers do not identify bioethics as a fundamental component of their fields of research, but the consequences of scientific advances are increasingly impacting on society. Society, particularly at the present time, where social networks take the place of reliable sources of information, lacks reliable information to enable informed debate on key issues such as abortion, gene editing and stem cell use. The debate gains prominence in several settings, from the academic to the politicians, through organized social movements and religious groups, especially when the debate focuses on the human embryo. In this article we want to demonstrate the relevance of the ontological question (from Greek ontos, being, and logos, science) in the scientific context and the need for an enlightened dialogue between science and society, aiming to construct a bioethics based on a hermeneutical ethics, of a reflection on the theories of the philosophers Jürgen Habermas and Hans Jonas.